THE CITY AND ITS SPATIAL TRANSFORMATIONS: A DIACHRONIC AND QUANTITATIVE ANALYSIS OF THE URBAN SPRAWL PROCESS. CASE STUDY OF TÉBESSA (ALGERIA) - Radhia Decha; Mohammed Cherif Adad (International Journal of Innovative Technologies in Social Science, 2024)
Urban sprawl is a significant phenomenon affecting many cities, including the city of Tebessa in Algeria. This spatial dynamic, characterized by often uncontrolled expansion of the urban fabric towards the peripheries, generates profound transformations in the morphology and functioning of cities. This article proposes an in-depth analysis of this process through a methodology combining diachronic analysis and spatial quantitative analysis. The objective is to model the percentage of built-up area as a function of distance from the historic core, using a logistic function. This approach highlights the transition between the compact urban fabric of the center and the dispersed periphery, thus offering a measure of urban dilution. The study reveals that Tebessa has undergone significant spatial transformation since independence, transitioning from a compact urban morphology to a more extensive urban sprawl. The results demonstrate a gradual decrease in building density radiating outward from the center, illustrating the phenomenon of spatial dilution. Although urban expansion continues, its pace tends to stabilize. This research underscores the utility of the logistic model for understanding and forecasting urban growth dynamics, offering a new perspective on the spatial evolution of cities.